2021
DOI: 10.3390/biomedicines9030257
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Signatures Associated with Bronchopulmonary Dysplasia Severity in Tracheal Aspirates of Preterm Infants

Abstract: Bronchopulmonary dysplasia (BPD) is a form of chronic lung disease that develops in neonates as a consequence of preterm birth, arrested fetal lung development, and inflammation. The incidence of BPD remains on the rise as a result of increasing survival of extremely preterm infants. Severe BPD contributes to significant health care costs and is associated with prolonged hospitalizations, respiratory infections, and neurodevelopmental deficits. In this study, we aimed to detect novel biomarkers of BPD severity… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 93 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…The exclusion criteria were as follows: (a) patients with no presumed clinical diagnosis, (b) patients with critical illnesses other than BPD, and (c) patients with incomplete RNA data, including transcriptional data of miRNA and mRNA. miRNAs that were coexpressed among the datasets, including GSE156055 [ 13 ], GSE165828 [ 14 ], and GSE108604 [ 15 ], were identified and subsequently analysed. The GSE156055 dataset includes miRNA profiles in tracheal aspirates (TAs) from 51 infants who underwent invasive mechanical ventilation.…”
Section: Methodsmentioning
confidence: 99%
“…The exclusion criteria were as follows: (a) patients with no presumed clinical diagnosis, (b) patients with critical illnesses other than BPD, and (c) patients with incomplete RNA data, including transcriptional data of miRNA and mRNA. miRNAs that were coexpressed among the datasets, including GSE156055 [ 13 ], GSE165828 [ 14 ], and GSE108604 [ 15 ], were identified and subsequently analysed. The GSE156055 dataset includes miRNA profiles in tracheal aspirates (TAs) from 51 infants who underwent invasive mechanical ventilation.…”
Section: Methodsmentioning
confidence: 99%
“…[32][33][34] For example, miRNA-148a, the top three miRNAs in terms of abundance in bovine and human milk, can target binding to the SIRT1 gene, attenuate the inflammatory response caused by NF-κB activation, and prevent the development of Necrotizing enterocolitis (NEC). 35,36 miR-30b-5p and miR-146a inhibit the production of interleukin-3 and interferon, thereby increasing the number of regulatory T cells and promoting the development of the immune system in newborn animals, and also have the potential to prevent bovine milk protein allergy early in life. [37][38][39] Therefore, continued homology studies for miRNAs in milk from different livestock animals, especially the analysis of miRNAs species and content between human milk and bovine milk, will be of great value for the future improvement of infant formula, and the functional assessment of miRNAs in milk and milk products.…”
Section: Types and Content Of Milk-derived Mirnasmentioning
confidence: 99%
“…FOXD2-AS1 accumulates in GC and is upregulated in GC cells and positively correlates with large tumour size, advanced pathological stage, and poor prognosis [35,36]. Gene set enrichment analysis in Gene Expression Omnibus (GEO) datasets revealed that cell cycle and DNA replicationassociated genes were enriched in patients with high FOXD2-AS1 expression [37]. Loss of FOXD2-AS1 function inhibited cell growth through cell cycle inhibition in GC, while upregulation of FOXD2-AS1 expression promoted cancer progression [38,39].…”
Section: Lsd1 and Long Noncoding Rna Foxd2-as1mentioning
confidence: 99%